RME-Based Online Learning On The Fourth Class Student’s Mathematics Learning Motivation - Sholeha, Herisa; Sujati, Heronemus; Muhaimin, Asrofi Abdul (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
Study purpose. This study aims to analyze the effect of Realistic Mathematics Education (RME)-based online learning on the learning motivation of fourth-grade elementary school students. Materials and Methods. This study used a quantitative, survey-based approach. The study population consisted of 840 fourth-grade elementary school students in Dukuntang Regency. The sample was selected using a simple random sampling method, resulting in 271 students as respondents. Data were collected through the distribution of a validated learning motivation questionnaire and an interview guide to strengthen the quantitative findings. Data analysis techniques included descriptive and inferential analysis, including normality and linearity tests, as well as regression analysis, to determine the effect of RME-based online learning variables on student learning motivation. Results. The results showed that RME-based online learning increased student learning motivation by up to 85%, or in the high category, indicating that this approach is effective in helping students understand mathematics material in a more contextual and meaningful way. Conclusion. RME-based online learning is recommended as a strategy to increase student learning motivation at the elementary school level.